The construction defect issue involving method of rectified of double storey house / Amir Fakhrullah Ahmad Asmadi - Ahmad Asmadi, Amir Fakhrullah (Universiti Teknologi MARA, Perak, 2019)
The construction industry is one of the largest contributors to the nation's economy. It includes the development of residential areas where many of developer now running the potential land that will become a new city. Unfortunately, all the developers and contractors face the same issue after they hand over the house. It is normal for a building or house to have a defect after construction. The focus of this report is to identify and learn about the type of defect, the factor of defect and method of the rectified defect. Some of defects that emerge in this case study at Taman Klebang Putra and Taman Meru Perdana more to non-structural defect like plastering crack, leaking and dampness at slap porch. This happened because of 3 main problems. The first problem is regarding people, where there is a lack of supervision and poor workmanship. Second is on material and design, which they applied the low-quality material because of the low price and not follow the exact specification.